AAV8-mediated sVEGFR2 and sVEGFR3 gene therapy combined with chemotherapy reduces the growth and microvasculature of human ovarian cancer and prolongs the survival in mice - Kujala, Anni; Valkonen, Elina; Sallinen, Hanna; Tuppurainen, Laura; Laakso, Hanne; Ylä-Herttuala, Elias; Liimatainen, Timo; Kujala, Jouni; Jokelainen, Otto; Sironen, Reijo; Anttila, Maarit; Ylä-Herttuala, Seppo (Frontiers in Medicine, 2022)
Background Vascular endothelial growth factors (VEGFs) are major regulators of intratumoral angiogenesis in ovarian cancer (OVCA). Overexpression of VEGFs is associated with increased tumor growth and metastatic tendency and VEGF-targeting therapies are thus considered as potential treatments for OVCA. Here, we examined the antiangiogenic and antitumoral effects on OVCA of adeno-associated virus 8 (AAV8)-mediated expression of soluble VEGF receptors (sVEGFRs) sVEGFR2 and sVEGFR3 together with paclitaxel and carboplatin chemotherapy. Materials and methods Immunodeficient mice were inoculated with human OVCA cell line SKOV-3m. Development of tumors was confirmed with magnetic resonance imaging (MRI) and mice were treated with gene therapy and paclitaxel and carboplatin chemotherapy. The study groups included (I) non-treated control group, (II) blank control vector AAV8-CMV, (III) AAV8-CMV with chemotherapy, (IV) AAV8-sVEGFR2, (V) AAV8-sVEGFR3, (VI) AAV8-sVEGFR2 and AAV8-sVEGFR3, and (VII) AAV8-sVEGFR2 and AAV8-sVEGFR3 with chemotherapy. Antiangiogenic and antitumoral effects were evaluated with immunohistochemical stainings and serial MRI. Results Reduced intratumoral angiogenesis was observed in all antiangiogenic gene therapy groups. The combined use of AAV8-sVEGFR2 and AAV8-sVEGFR3 with chemotherapy suppressed ascites fluid formation and tumor growth, thus improving the overall survival of mice. Antitumoral effect was mainly caused by AAV8-sVEGFR2 while the benefits of AAV8-sVEGFR3 and chemotherapy were less prominent. Conclusion Combined use of the AAV8-sVEGFR2 and AAV8-sVEGFR3 with chemotherapy reduces intratumoral angiogenesis and tumor growth in OVCA mouse model. Results provide preclinical proof-of-concept for the use of soluble decoy VEGFRs and especially the AAV8-sVEGFR2 in the treatment of OVCA.